Synthesis and X-Ray Single Crystal Structures of Cadmiym(II) Complexes: CdCl2[CS(NHCH3)2]2 and CdCl2(CS(NH2)NHC6H5)4-Single Source Precursors to CdS Nanoparticles - M. J. Moloto; N. Revaprasadu; G. A. Kolawole; P. O’brien; M. A. Malik; M. Motevalli (E-Journal of Chemistry)
Two new cadmium(II) complexes CdCl2[CS(NHCH3)2]2 (1) and CdCl2(CS(NH2)NHC6H5)4 (2) have been synthesized and characterized by spectroscopic and x-ray crystallographic methods. Both compounds are monomers in the solid state with the four and six coordinate and their coordination geometries based on distorted tetrahedron and distorted octahedron respectively. The thiourea ligands behave as monodentate in both compounds with the binding through sulfur. Complex (2) is one of the few examples of monomeric six coordinate Cd(II) complexes with four monodentate thiourea and two chloride ligands. The Cd-S bond proved useful as a source of preparing nanoparticles using these complexes as single source precursor at a temperature of 250 °C in trioctylphosphine oxide (TOPO).